2017
DOI: 10.1111/1467-8551.12265
|View full text |Cite
|
Sign up to set email alerts
|

Incentives, Resources and Combinations of Innovation Radicalness and Innovation Speed

Abstract: Although scholars have independently explored the antecedents of innovation radicalness and innovation speed, this study's focus on combinations of radicalness and speed offers a number of new insights. Drawing on a comparative case study approach of ten innovation departments of large organizations, the authors’ findings provide evidence that intrinsic rewards trigger innovation radicalness, but the simultaneous presence of extrinsic rewards diminishes innovation speed. Further, the authors show that the avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…Tangible Extrinsic clearly suggests that while incentive-motivation linkages are multiplex, intrinsic motivation ultimately mediates organizational innovativeness. Overall, these results support earlier claims that intrinsic motivation is a key driver of creativity (Amabile, 1993(Amabile, , 1996Amabile et al, 1996;Amabile and Pratt, 2016;Ankli and Palliam, 2012;Behrens and Patzelt, 2018;Cho andPerry, 2011: Ryan andDeci, 2000).…”
Section: Intrinsicsupporting
confidence: 89%
See 2 more Smart Citations
“…Tangible Extrinsic clearly suggests that while incentive-motivation linkages are multiplex, intrinsic motivation ultimately mediates organizational innovativeness. Overall, these results support earlier claims that intrinsic motivation is a key driver of creativity (Amabile, 1993(Amabile, , 1996Amabile et al, 1996;Amabile and Pratt, 2016;Ankli and Palliam, 2012;Behrens and Patzelt, 2018;Cho andPerry, 2011: Ryan andDeci, 2000).…”
Section: Intrinsicsupporting
confidence: 89%
“…However, achieving such organizational environment is not easy. For instance, managers face many challenges in identifying optimal ways of motivating their employees to complete tasks (Behrens and Patzelt, 2018;Faisal Ahammad et al, 2015;Stajkovic and Luthans, 2003), share knowledge, contribute new ideas and take initiatives (Foss et al, 2009(Foss et al, , 2015Minbaeva et al, 2003). Employees also respond differently to managerial practices and incentives, and motivational processes vary across different organizational cultures and environments (Krausert, 2014;Shalley et al, 2000;Ryan and Berbegal-Mirabent, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence also revealed that there was a link between HPWS and firm innovation ( RQ3 ). In particular, the managers claimed that people are a contributor to organizational success because if organisations invest in developing employees’ knowledge, skills and motivation, they will then return their effort to contribute to firm innovation (also see Behrens and Patzelt, 2018). For innovation to occur, organisations might leverage human capital to advance firm expertise for developing new products and services (Bouncken et al , 2018; Chen and Huang, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…15405/epsbs.2021.04.29 Corresponding Author: Natalya Gagulina Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 273 development. In such conditions, competence, innovators' creativity, effective system of including the results of intellectual activity, advanced innovative infrastructure (Behrens & Patzelt, 2018).…”
Section: The Main Role Of Intellectual Technologies In the Modern Economymentioning
confidence: 99%